Submission for Special Issue: The Role of Platelet Activation in the Pathophysiology of HIV, Tuberculosis, and Pneumococcal Disease. Bedaquiline Suppresses ADP-Mediated Activation of Human Platelets In Vitro via Interference With Phosphatidylinositol 3-Kinase - Tintinger, Gregory R.; Theron, Annette J.; Steel, Helen C.; Cholo, Moloko C.; Nel, Jan G.; Feldman, Charles; Anderson, Ronald (Frontiers in Immunology, 2021)
Although bedaquiline has advanced the treatment of multidrug-resistant tuberculosis (TB), concerns remain about the cardiotoxic potential of this agent, albeit by unexplored mechanisms. Accordingly, we have investigated augmentation of the reactivity of human platelets in vitro as a potential mechanism of bedaquiline-mediated cardiotoxicity. Platelet-rich plasma (PRP) or isolated cells prepared from the blood of healthy, adult humans were treated with bedaquiline (0.625 -10 µg/ml), followed by activation with adenosine 5’-diphosphate (ADP), thrombin or the thromboxane A2 receptor agonist (U46619). Expression of platelet CD62P (P-selectin), platelet aggregation, Ca2+ fluxes and phosphorylation of Akt1 were measured using flow cytometry, spectrophotometry, fluorescence spectrometry and by ELISA procedures, respectively. Exposure to bedaquiline caused dose-related inhibition of ADP-activated, but not thrombin- or U46619-activated, expression of CD62P by platelets, achieving statistical significance at a threshold concentration of 5 µg/ml and was paralleled by inhibition of aggregation and Ca2+ mobilization. These ADP-selective inhibitory effects of bedaquiline on platelet activation were mimicked by wortmannin, an inhibitor of phosphatidylinositol 3-kinase (PI3-K). These overlapping, selective inhibitory effects of bedaquiline and wortmannin on ADP-activated platelets implicated PI3-K as being a common target, a contention confirmed by the observed inhibitory effects of bedaquiline on the phosphorylation of Akt1 following activation of platelets with ADP. These apparent inhibitory effects of bedaquiline on the activity of PI3-K may result from the secondary cationic amphiphilic properties of this agent. If operative in vivo, these anti-platelet effects of bedaquiline may ameliorate the risk of TB-associated cardiovascular disease.